GEN-Z'S CONSUMPTIVE BEHAVIOR TOWARDS THE TREND OF YOU LIVE ONLY ONCE TO YOU NEED ONLY ONE IN THE PERSPECTIVE OF ISLAMIC BUSINESS ETHICS - Anggraini, Misi (Journal of Management and Islamic Finance, 2025)
This study explores the shift in consumptive behaviour among Generation Z from the "You Live Only Once" (YOLO) trend to "You Need Only One" (YONO) through the lens of Islamic business ethics. Employing a qualitative research design, data were collected via in-depth interviews and netnographic observation of social media activities. Findings reveal that the YONO trend reflects a growing ethical awareness and preference for mindful consumption, influenced by Islamic values emphasizing moderation, responsibility, and sustainability. The discussion highlights how this transition challenges conventional consumption patterns and offers insights into integrating ethical considerations in Gen Z’s consumer behaviour, contributing to both individual well-being and social welfare. This research provides critical implications for marketers, policymakers, and scholars interested in ethical consumption and Islamic business principles.